Wokół kompetencji diagnostycznych nauczyciela wychowania przedszkolnego - w poszukiwaniu optymalnych rozwiązań w zakresie diagnozowania gotowości szkolnej dziecka = Discussing the diagnostic competence of a pre-school education teacher - in search of optimal solutions for the diagnosis of school readiness of a child - Kochanowska, Ewa (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
The following article is an attempt to justify the thesis saying that the teacher`s diagnostic competencies, which should not be used as a tool for labeling children as ready / not ready for school education, but rather as a factor of monitoring children?s development and needs, play a key role in diagnosing children`s school readiness in a multidimensional and continuous manner.
Keywords: diagnoza; kompetencje nauczyciela; gotowość szkolna; model diagnozy; diagnosis; teacher`s competencies; school readiness; diagnosis model